Representations of Mythological Rituals and Actions in Kurdish Oral Narratives - Shahnaz Tahmasbi (پژوهشنامه ادبیات کردی)
Kurdish folk poems, known as Kurdish verses, constitute the oldest part of Kurdish literature. Within these works, rich in themes of love and epic tales, are depictions of important mythological elements that have maintained their ancient essence. The protagonist of these poems encounters actions and rituals imbued with a mythological essence, mirroring similar occurrences found in the mythological narratives of Iran and other cultures worldwide. The most prominent of these poems are: "Khaj and Siamand," "Las and Khazal," "Mam and Zain," "Saidavan," "Sheikh Farkh and Khatun Asti," and "Sheikh Mand and Sheikh Rash." Using a descriptive-analytical approach, this study examines the mythological rituals and actions presented in Kurdish oral poems. The findings suggest that certain mythological actions and rituals, with universal significance, are depicted in Kurdish oral verses. The findings of the research show that extraordinary birth, dragon killing, son killing, rite of passage, and initiation, which are associated with enduring many sufferings and hardships, are represented in these poems, and it shows that many of the basic human needs everywhere and at any time are very similar to each other. The research findings reveal that themes such as miraculous births, dragon killing, son killing, rites of passage, and initiations involving trials and tribulations are portrayed in these poems. This demonstrates the universal similarity of basic human experiences across different cultures and eras.